Effects of environmental and genetic interactions on job burnout in coal miners: interactions between occupational stress, coping styles, and NR3C2 gene polymorphisms - Lin, Xin; Ma, Xiaofan; Yi, Xiaoting; Qu, Chao; Li, Fuye (Frontiers in Public Health, 2023)
Objectives To investigate the current situation regarding occupational burnout among coal miners, explore the relationship between NR3C2 gene polymorphism and occupational burnout, and analyze the influence of the interaction between environment and gene on occupational burnout. This study provides a scientific basis for formulating health strategies to combat job burnout. Methods A total of 1,500 first-line coal mine workers were selected by cluster random sampling, and the job burnout scale, job content questionnaire (JCQ), and simplified coping style questionnaire (SCSQ) were used for the questionnaire survey. A total of 150 workers were randomly selected from the high burnout group and the low burnout group, and a total of 300 workers were selected as the research objects to examine the relationship between gene polymorphism, environment-gene interactions and burnout. This study employed iMLDRTM genotyping technology for NR3C2 gene (rs5522, rs2070950) polymorphism analysis. The relationship between the occurrence of job burnout, occupational stress, coping styles and the NR3C2 gene was analyzed. Results Finally, a total of 1,282 valid questionnaires were retrieved, with an effective recovery rate of 85.5%. The study included 128 participants (10%) with zero burnout, 400 (31.2%) with mild burnout, 649 (50.6%) with moderate burnout and 105 (8.2%) with severe burnout. There were significant differences in the rate of burnout among miners with respect to sex, age, working years, educational level, shifts, and marital status (P < 0.05). The difference in occupational stress between the different job burnout groups was statistically significant (P < 0.05). Compared with the GG genotype of rs2070950 of the NR3C2 gene, the CC genotype was identified as a susceptibility gene for occupational burnout (P < 0.05). In respect to rs5522, rs2070950, occupational stress, positive coping, and negative coping, the low-risk group was unlikely to suffer from job burnout compared with the high-risk group (OR = 0.103, 95%CI: 0.058–0.182). Conclusion In addition to demographic characteristics, occupational stress and negative coping styles were also identified as risk factors for job burnout. The interaction between locus rs5522, locus rs2070950, occupational stress, positive response, and negative response were found to affect the incidence of occupational burnout.